Experimental study and elastic visco-plastic modelling of the time-dependent stress-strain behaviour of Hong Kong marine deposits - Zhu, Jungao (The Hong Kong Polytechnic University, 2000)
xxvii, 319 leaves : ill. 30 cm. PolyU Library Call No.: [THS] LG51 .H577P CSE 2000 Zhu The studies in this thesis have focused on two interrelated areas:- (1) experimental investigation on strain-rate effects, creep behaviour and stress relaxation of remoulded Hong Kong marine deposits (RHKMD); (2) examination and development of time-dependent constitutive models and applications of these constitutive models in fully coupled consolidation analyses of geotechnical structures on soft ground. A large number of tests on remoulded HKMD have been conducted. These tests include (a) conventional triaxial tests shearing at various strain rates (ranging from ±0.15%/h to ±15%/h), (b) triaxial creep tests (both drained and undrained creep), and (c) triaxial stress relaxation tests. The strain rate-dependency, creep and stress relaxation behaviour of RHKMD are investigated extensively and systematically. From the experimental investigation, it is found that the remoulded HKMD exhibits viscous effects, albeit not as pronounced as those of other natural sensitive clays. The undrained shear strength for the specimens of RHKMD tested with OCR=1 to 8 increases by 5.5% and 8.4% for a tenfold change in strain rate for compression and extension tests, respectively. The strain-rate effects are more significant for extension tests than the effects for compression tests. In both undrained compression and extension multi-staged triaxial creep tests, the log(εa)-log(t) relationship at lower stress levels is linear, and the slopes of these lines are dependent on current deviator stress as well as stress history. From the drained triaxial creep test results, two empirical equations are proposed for the relationships of deviator and volumetric strains versus time. From results of undrained triaxial stress relaxation tests, it is found that, at failure, the relaxation behaviour is almost independent of the shear type (compression or extension) of tests, but dependent on the shear strain rate before the relaxation test starts. In a multi-staged relaxation test, the lower the stress level, the larger the decay of deviator stress. A power law equation is proposed to compute the decay of deviator stress. A three-dimensional (3-D) Elastic Visco-Plastic (EVP) model proposed by Yin and Graham (1999) is firstly examined and verified by simulating a number of triaxial tests. The capability of the model is verified. The 3-D EVP model is incorporated into a finite element (FE) program. A parametric study using this FE program with the 3-D EVP model is then carried out to analyse an ideal foundation on HKMD in a plane strain condition. In the FE modelling, the foundation soil is considered as an elastic visco-plastic material described by the EVP model. It is found that, in an elastic visco-plastic soil, the so-called abnormal increase of porewater pressure after the completion of loading may result from either the Mandel-Cryer effect or viscous effects, or both of them depending on boundary conditions. When viscosity of soil is considered, the porewater pressure in soil will be higher than that without consideration of the viscosity. The larger the creep parameter ψ/v and lower permeability, the higher the porewater pressure and the larger the deformation in clays. The influence of the viscous effects on the lateral displacement is relatively weak. The FE program with the 3-D EVP model is also used to analyse porewater pressure responses and deformation in clay underneath an island - Tarsiut Island in the Canadian Beaufort Sea. The abnormal increase of porewater pressure after the completion of construction has been successfully simulated. Yin and Graham's (1999) 3-D EVP model is extended in this thesis. The extended 3-D EVP model is validated by comparing the predicted results with laboratory measured results. This model is formulated in a general 3-D stress state, and can simulate the stress-strain-time behaviour of both overconsolidated and normally consolidated soils. This extended 3-D EVP model is implemented in the FE program, and then is used to analyse the consolidation behaviour of the foundation soils underneath a test embankment at the new airport of Hong Kong. The results of the FE simulation agree well with the observed data. The long-term deformation of the test embankment is properly simulated. A framework of a 3-D EVP model for anisotropically consolidated clay is proposed. This model is based on the original Cam-clay model and the concept of "equivalent time". The constitutive relationship is formulated. The validity of the model is then briefly verified by comparing model predictions to test results. Department of Civil and Environmental Engineering Ph.D., Dept. of Civil and Structural Engineering, The Hong Kong Polytechnic University, 2000. Doctorate